PENGARUH KECERDASAN SPIRITUAL, KINERJA PELAYANAN PERPAJAKAN, KETEGASAN SANKSI PERPAJAKAN DAN PENYELEWENGAN PAJAK TERHADAP MOTIVASI WAJIB PAJAK DALAM MEMENUHI KEWAJIBAN PERPAJAKAN (Studi Empiris Pada Wajib Pajak Orang Pribadi Di KPP Pratama Pekanbaru Tampa - Devi Andriyani; Zirman '; Sem Paulus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The purpose of this research is to analyze the influence of the spiritual quotient, tax services performance, firmness tax penalties, and tax fraud towards the motivation tax from payers in fulfilling tax obligatory at tax office of Pratama Tampan Pekanbaru. The data in this study is the primary data. The population in this study were the tax obligatory personality with criteria less pay that registered in the tax office of Pratama Tampan Pekanbaru. The sampling method used in this study saturated purposive sampling method. Data collected from 100 respondents people become tax obligatory personality less pay. The method of data analysis used to the test the hypotesis is multiple regression analysis by using SPSS 20 version. The results of this research showed that spiritual quotient variable, tax services performance, firmness tax penalties, and tax fraud towards individually influence significant towards the motivation tax from payers in fulfilling tax obligatory at tax office of Pratama Tampan Pekanbaru. Simultaneously, independent variabel’s influence towards the motivation tax from payers in fulfilling tax obligatory as a dependent variabel’s. The magnitude of the effect caused by Adjusted R² by four variables is 39% of the dependent variable, while the remaining 61% is influenced by other independent variabel that are not observed in this study.Keywords : Spiritual quotient, tax services performance, firmness tax penalties, tax fraud, and tax payers motivation.